Correlation between the Stature and Head Length among Undergraduate Medical Students in a Medical College of Eastern Nepal - Sah, Sanjib Kumar; Parajuli, Surya Bahadur; Adhikari, Rakesh Kumar; Bhakta, Shalini (Birat Journal of Health Sciences, 2025)
Introduction: Stature is a crucial parameter in forensic and anthropological sciences used for personal identification. It has a significant biological correlation with various body parts, including head length. The current study aims to determine whether a statistically significant relationship exists between the stature and head length of undergraduate medical students. Objective: The objective of this study was to assess the correlation between the stature and head length among undergraduate medical students in eastern Nepal. Methods: A cross-sectional study was conducted from January 15, 2024 to January 30, 2024 at Birat Medical College Teaching Hospital, Tankisinuwari, Morang, Nepal. A total of 135 preclinical nepali medical students were selected using census sampling. Ethical clearance was taken from the Institutional Review Committee (IRC) of Birat Medical College Teaching Hospital. Informed consent was taken from individual students. A pro forma was used to record data. Stature was measured using a stadiometer and head length using a sliding caliper. The collected data was entered in Microsoft Excel 2016 and analyzed by SPSS version 25. Results: The overall mean stature was 163.99±9.67 cm and mean head length was 18.08±0.91 cm. Males had a mean height of 171.42±6.32 cm and mean head length of 18.61±0.80 cm; females had 156.66±6.17 cm and 17.57±0.70 cm, respectively. A moderate positive correlation was found between stature and head length (r = 0.532, p < 0.001). Gender-wise, the correlation was weak and non-significant in males (r = 0.10, p = 0.41), and weak to moderate but significant in females (r = 0.27, p = 0.02). Conclusion: A statistically significant moderate positive correlation exists between stature and head length among the students, more so among females.